2020
DOI: 10.31227/osf.io/rgdup
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RELATIONSHIP BETWEEN THE KNOWLEDGE ON SELF-EFFICACY ABOUT COUNSELING AND STOMA SITE MARKING FOR PATIENTS UNDERGOING STOMA SURGERY IN ETNs

Abstract: Stoma complications may affect physical and psychological aspects in patients’ life. The implementation of counseling and stoma site marking prior to surgery can reduce the risk of complications and improve the quality the life of the patients. Enterostomal Therapy Nurse (ETN) is a nurse graduated of an educational program called ETNEP (Enterostomal Therapy Nurse Education Program). Self-efficacy of ETNs plays vital role in application of counselling and stoma site marking. This study aimed to evaluate knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The American Cancer Society, 2017 reported that colorectal cancer is the third common cancer type and became the second cause of death worldwide (American Cancer Society, 2017). The number of patients performed stoma surgery is increasing with about one million people living in North America with permanent stoma, and more than 120,000 new stomas are performed each year (Putri, et al, 2018). According to the National Cancer Institute in Egypt, approximately 650,000 adults in Egypt currently have a stoma and about 3000 new surgeries are performed each year with colostomy (El Sayed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The American Cancer Society, 2017 reported that colorectal cancer is the third common cancer type and became the second cause of death worldwide (American Cancer Society, 2017). The number of patients performed stoma surgery is increasing with about one million people living in North America with permanent stoma, and more than 120,000 new stomas are performed each year (Putri, et al, 2018). According to the National Cancer Institute in Egypt, approximately 650,000 adults in Egypt currently have a stoma and about 3000 new surgeries are performed each year with colostomy (El Sayed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini sesuai dengan penelitian yang dilakukan di Saudi Arabia yang menunjukan bahwa partisipasi pelatihan dan pendidikan kesehatan tentang perawatan stoma pada pasien oleh tenaga kesehatan memiliki pengaruh terhadap pengetahuan perawatan stoma . Peran perawat enterostomal juga dinilai memiliki pengaruh dalam memberikan konseling awal pada masa preoperative untuk meningkatkan self-efficacy dan pengetahuan pasien (Putri et al 2018). Kondisi ini juga diungkapkan dalam temuan lain yang membahas dampak penandaan stoma site pada saat preoperatif dapat meningkatkan perawatan diri dan kualitas kesehatan pasien (Kim, Jang, dan Lee 2021).…”
Section: Pembahasanunclassified